Moderation of the relationship between the error-related negativity and anxiety by age and gender in young children: A preliminary investigation. (October 2019) - Ip, Ka I; Liu, Yanni; Moser, Jason; Mannella, Kristin; Hruschak, Jessica; Bilek, Emily; Muzik, Maria; Rosenblum, Katherine; Fitzgerald, Kate
Highlights: Age and gender moderate associations between ERN and anxiety in youth. Smaller ERN associated with more anxious symptoms in preschool-aged girls. A larger ERN associated with more anxious symptoms in school-aged girls. Abstract: The error-related negativity (ERN) is a neurophysiologic response to errors that associates with anxiety. Despite the potential relevance of the ERN for understanding mechanisms of early anxiety problems in the developing brain, the relation between ERN and anxious symptoms in young children remains poorly understood. Emerging evidence suggests that ERN-anxiety associations could vary by developmental stage, but this work requires replication and consideration of gender effects, given earlier maturation of the ERN and higher rates of anxiety problems in girls relative to boys. To address this gap, the ERN was collected in 49 preschool- to school-aged children (ages 4–9; 26 girls) sampled across a wide range of anxiety severity. Regression analyses revealed that ERN - anxiety associations depended on age and gender. Specifically, larger (more negative) ERN associated with more anxiety in older girls, whereas smaller ERN associated with more anxiety symptoms in younger girls. No ERN-anxiety association was found in boys. These findings suggest that age and gender moderate the direction of the relation between ERN and anxiety in early childhood and could have important implications for the development of ERN-based risk identification and targeted treatment strategies tailored to individual children.